Surface pattern classification and applications - Tai, Ruiwen (Nanyang Technological University, 2023)
This study investigates the parameters which affect the liquid spreading properties of surface patterns by examining the contact angles of water droplets. The study was conducted using copper surface patterns to determine how factors such as geometric layout, type of surface pattern, and height affect contact angles. Surface replication with polycaprolactone (PCL) was also carried out to overcome limitations arising from machining. From the results, it is observed that these parameters have a significant impact on the contact angle of liquid droplets, thus influencing the liquid spreading properties of the surface patterns. These findings provide insight on the mechanism of liquid spreading behaviours, which are present in natural phenomena and also important for industrial applications.